2021
DOI: 10.21203/rs.3.rs-640850/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Survey of Knowledge, Perceptions and Use of Core Outcome Sets among Clinical Trialists

Abstract: Introduction: Core outcome sets (COS) are standardised sets of outcomes, which represent the minimum outcomes that should be measured and reported in clinical trials. COS can enhance comparability across health trials by reducing heterogeneity of outcome measurement and reporting, and potentially minimising selective outcome reporting. Examining what researchers involved in trials know and think about COS is essential to increase awareness and promote COS uptake. The aim of this study is therefore to examine c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Identification of low COS use in this cohort of trials is consistent with previous examinations 13,14 . One possible explanation may be low levels of knowledge about the existence and value of COS 15 . This is reflected in survey responses indicating that knowledge about COS is important for COS use.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Identification of low COS use in this cohort of trials is consistent with previous examinations 13,14 . One possible explanation may be low levels of knowledge about the existence and value of COS 15 . This is reflected in survey responses indicating that knowledge about COS is important for COS use.…”
Section: Discussionmentioning
confidence: 99%
“…The COMET guidelines recommend measuring and reporting all COS outcomes as the minimum in trials 3 . A previous survey of trialists with a trial registered on the ISRCTN repository found that fewer than half of respondents who had used a COS in a trial reported including all COS outcomes 15 . In addition to poor COS knowledge, lack of full COS use and/or reporting in the current study may be due to trialists perceiving identified COS as not relevant or valid for use.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations